In vitro gastrointestinal digestion of microencapsulated extracts of Flourensia cernua, F. microphylla, and F. retinophylla - Rodríguez, D. Jasso de (2019)
Recently, some species of the genus Flourensia have been identified by their potential health effects (e.g. anti-inflammatory and apoptotic). Encapsulation of plant extracts is a process that can allow an adequate dosage administration, as well as to protect bioactive compounds and improve their controlled release in the gastrointestinal (GI) system. Therefore, the aims of this work were: to microencapsulate the ethanol extracts of F. cernua, F. microphylla, and F. retinophylla; and to evaluate the controlled release of the microencapsuled extracts in an in vitro GI system. Leaves of Flourensia spp. were collected in wild sites of Coahuila State, and the ethanol extracts were obtained by the Soxhlet method. The encapsulation was performed by the gelation technique, using alginate. The microcapsules formed were characterized in terms of total phenol content (Folin-Ciocalteu method), antioxidant activity by the 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis (3-ethylbenzthiazoline-6-sulphonic) diammonium acid (ABTS), and the ferric reducing antioxidant power (FRAP) assays, scanning electron microscopy (SEM), and thermal analysis, and in vitro GI digestion. The microcapsules were found to have spherical-shape and a micro-scale dimension in the range of 2.168.8??m. Also, the built of microcapsules was confirmed by the appearance of an exothermic peak centered at 600?°C in the DSC analysis. F. microphylla noted for its strong antioxidant activity, even in its encapsulated form. In the gastric system the extracts of fresh microcapsules were released from 7.7% to 14.5%, while values of 26.5% to 53.3% were observed for those dried. For the intestinal system, the higher release was observed for dried microcapsules (59.9% to 78.4%) than for those fresh (26.3% to 30.2%). Thus, it was demonstrated that the alginate microcapsule protected the extracts until they were delivered to the target site in the GI model, and this effect was better with the dried microcapsules of Flourensia spp. This study would set the guide for the application of Flourensia spp. extracts in order to take advantage of their benefits to human health.